Modeling of genetic processes underlying the development of resistance to fipronil in the Colorado potato beetle (Leptinotarsa decemlineata Say) - K. A. Kitaev; I. S. Mardanshin; E. V. Surina; T. I. Leontieva; M. B. Udalov; G. V. Benkovskaya (Вавиловский журнал генетики и селекции)
The main method of pest control is by applying chemical insecticides. The efficacy of insecticides is reduced due to the development of resistance by pest populations. This is an especially important problem with the Colorado potato beetle. There are different strategies for the use of insecticides to slow the development of resistance. Based on long lasing research, we propose a hypothesis about delaying the development of resistance by applying insecticides at low doses. To test this hypothesis, we have built predictive discrete genetic models of resistance in Colorado potato beetle populations. The model based on the classical equations of population genetics has been supplemented by various factors. Calculations of the survival rates of Colorado potato beetle individuals were carried out taking into account the statistical regularities of the distribution of the toxic substance after treatment by insecticides. We have calculated the survival rates of different genotypes using a lognormal distribution after changing the insecticide dose two-fold or more. The factor of differentiated mortality during the winter was additionally introduced into the model. The use of phenetic markers of nonspecific resistance to environmental factors allowed us to compute the model with mediated intergenic interactions. Various hypotheses about strategies in overcoming resistance have been tested using this model. Calculations demonstrated that the use of insecticides at minimum effective doses (low dose) leads to a slower increase in the proportion of resistant individuals in populations of the Colorado potato beetle for two seasons. Resistance develops much more slowly following alternate treatment with insecticides from different chemical classes. The best strategy is through off-season treatment with insecticides of different chemical classes at lower doses.